The use of propolis as an adjunct to periodontal treatment (Research, Society and Development, 2021)
Periodontal disease (PD) is defined as a multifactorial polymicrobial infection that results in a chronic inflammatory process that affects the protective and supportive tissues of the teeth, which can result in the loss of the tooth element. The introduction of the use of antimicrobials as an adjunct to mechanical therapy becomes a therapeutic option to improve oral hygiene. Natural products have been increasingly used for chemical control of dental biofilm. Among them, propolis stands out, which is a resinous component collected by bees from different parts of the plants, several studies prove the activity of propolis as a preventive agent for caries and in the treatment of periodontal diseases, in addition to having bactericidal, fungal and anti-inflammatory. The aim of this study is to verify the effect of using propolis in the treatment of periodontal diseases, addressing means of use, advantages and disadvantages of propolis in periodontics, through a literature review. Searches were performed in the Scientific Electronic Library Online (SciELO), Virtual Health Library (VHL), US National library of Medicine, National Institutes of Health (PubMed) databases, Academic Google, as well as articles in databases of higher education institutions in the Brazil. According to the data available in the literature, it can be concluded that the use of propolis as an adjunct to periodontal mechanical treatment in patients with periodontal diseases has significant positive effects on clinical periodontal and microbiological parameters, since propolis has anti-inflammatory and antimicrobial activity.